Al-mu’jam Al-Aroby baina yadaik wa manhaju ta’līfihi - Almimbar, Alvi Huda; Dwi Kurnianto, Irawan; Bahruddin, Uril (Ukazh: Journal of Arabic Studies, 2024)
انتشرت القواميس ذات النماذج المختلفة في جميع أنحاء العالم كأحد العناصر الداعمة في تعلم اللغة، حيث تسهم في توفير وسيلة فعالة لفهم المفردات والتعبيرات. يُعتبر "كتاب العربية بين يديك" من القواميس البارزة في تعلم اللغة العربية، ويتميز بشموليته وترتيبه البنّاء للمعلومات.يهدف هذا البحث إلى استكشاف معجم العربية بين يديك، مسلطًا الضوء على تاريخ مؤلف القاموس وأهميته في تعلم اللغة. سيتم توضيح إجراءات استخدام القاموس وتحليل مزاياه وعيوبه. يسعى البحث لفهم كيف يسهم القاموس في تطوير مهارات اللغة العربية لدى المتعلمين وكيف يمكن استغلال كتاب العربية بين يديك بشكل أمثل في سياق تعلم اللغة. Dictionaries with various models have spread worldwide as essential tools in language learning, providing an effective means to understand vocabulary and expressions. Al-arobiyyah baina yadaik is considered one of the prominent dictionaries in learning the Arabic language, distinguished by its comprehensiveness and structured organization of information. This research aims to explore the Arabic dictionary baina yadaik. shedding light on the history of the author and the significance of the dictionary in language learning. The procedures for using the dictionary will be elucidated, and its advantages and disadvantages will be analyzed. The study seeks to understand how the dictionary contributes to the development of Arabic language skills among learners and how to optimize the use of al-arobiyyah baina yadaik in the context of language learning. Kamus dengan berbagai model telah tersebar di seluruh dunia sebagai salah satu elemen pendukung dalam pembelajaran bahasa, memberikan sarana efektif untuk memahami kosakata dan ekspresi. Kamus Al-Arobiyyah baina yadaik dianggap sebagai salah satu kamus terkemuka dalam pembelajaran bahasa Arab, ditandai dengan cakupannya yang luas dan struktur pengaturan informasinya yang terstruktur. Penelitian ini bertujuan untuk menjelajahi kamus Arab Al-Arobiyyah baina yadaik, menyoroti sejarah penulis dan signifikansinya dalam pembelajaran bahasa. Prosedur penggunaan kamus akan dijelaskan, dan kelebihan serta kekurangannya akan dianalisis. Penelitian ini bertujuan untuk memahami bagaimana kamus berkontribusi pada pengembangan keterampilan bahasa Arab para pelajar dan bagaimana memanfaatkan Kamus Arobiyyah baina yadaik secara optimal dalam konteks pembelajaran bahasa.